2001
DOI: 10.1183/09031936.01.00098501
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of interleukin-;5 in sputum by addition of protease inhibitors

Abstract: The measurement of interleukin (IL)-5 in sputum is problematic, with interfering factors affecting immunoassay. The authors investigated whether sputum proteases could be acting as interfering factors by studying the effect of protease inhibitors (PI) on sputum IL-5 measurement.Induced sputa from 20 subjects with asthma were divided into aliquots, processed with and without protease inhibitors (in low and high concentrations) and the levels of IL-5 (spiked and endogenous) measured by enzyme immunoassay were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…We have investigated whether and how DTE might interfere with the detection of eotaxin in sputum when using a commercial immunoassay. As a further step in validating the method, and after a report that proteases present in the airway lining fluid might have an effect on the stability and therefore detection of mediators such as IL-5, 13 we have addressed the question of whether there would be any benefit from adding protease inhibitors (PIs) to sputum processed with PBS. Finally, we have examined the effect of high-speed centrifugation during processing with respect to effects on cell contamination and eotaxin levels.…”
mentioning
confidence: 99%
“…We have investigated whether and how DTE might interfere with the detection of eotaxin in sputum when using a commercial immunoassay. As a further step in validating the method, and after a report that proteases present in the airway lining fluid might have an effect on the stability and therefore detection of mediators such as IL-5, 13 we have addressed the question of whether there would be any benefit from adding protease inhibitors (PIs) to sputum processed with PBS. Finally, we have examined the effect of high-speed centrifugation during processing with respect to effects on cell contamination and eotaxin levels.…”
mentioning
confidence: 99%
“…(The addition of CTAB is not recommended if other mediators are to be measured.) Processing sputum after addition of protease inhibitors has been shown to improve measurement of IL-5 (see appendix) [114].…”
Section: Factors Specific To the Soluble Mediatormentioning
confidence: 99%
“…STOCKLEY and BAYLEY [21] found that the addition of elastase to sputum resulted in decreased levels of secretory leucocyte protease inhibitor and MPO by immunoassay. The addition of protease inhibitors to sputum before processing has resulted in increased rates of detection and levels of IL-5, suggesting that proteases are interfering substances in some cases [114].…”
Section: What To Do If Validity Is Poormentioning
confidence: 99%
“…Several research groups have investigated modified sputum processing techniques to optimize biomarker recovery [66][67][68]. However, these processing techniques are not fully validated and most of them prevented recovery of other mediators from the samples.…”
Section: Biomarkers In Fluid Phasementioning
confidence: 99%